أهمية فعالية الإرسال في التنس الأرضي - معوض, وائل; ابراهيم, قاسم; رحال, يارا (Latakia University Journal -Medical Sciences Series, 2014)
هدف البحث الى دراسة أهميه فعالية الإرسال في التنس الأرضي وتم تطبيق الدراسة على 19 لاعب مصنف شاركوا في البطولات الدولية التالية (بطولة لندن للماسترز 2011 وبطولة هامبورغ 2013 وبطولة الصين المفتوحة 2013 وبطولة شنغهاي للماسترز 2013 ) وقد تم تحليل النتائج التي شهدتها مباريات البطولات وبعد التحليل تم التوصل الى النتائج التالية: إن دقة وفعالية الإرسال تلعب دورا حاسما في حسم نتيجة المباراة وخاصة عند تقارب مستوى اللاعبين حيث أن غياب التركيز وفقدان الدقة في الإرسال يزيد من عدد الاخطاء المزدوجة وبالتالي فقدان أشواط عديدة في المباريات وإكساب الخصم أشواط نظيفة بدون مجهود وكذلك اللاعب الذي يمتلك ارسالات ساحقة كثر في المباريات يكون دائما في موقع الهجوم وهذا تأكيد على أن الفعالية القوية للإرسال تربك المنافس وتجعله يحتل موقع الدفاع دائما. This research aims to study the importance of serving efficiency in tennis. It is applied to nineteen labeled players, who have participated in the following international championships: 1-Masters-tennis tournament 2011 London; 2-Hamburg Tennis tournament; -3-china open tennis tournament2013 4-shanghai rolex masters 2013. Results of these tournaments have been analyzed and yielded the following results: the accuracy and efficiency of surving play a critical role in determining the result of the game, especially when levels of the two players are very close. Absence of focus and loss of accuracy in serving leads to increase in the number of double fault. That in turn leads to losing too many rounds in games and it also leads contender to win faultless rounds without any effort. When the player has too many aces in games, he will always be in attacking position. This is a conformation, which proves that the powerful efficiency of serving is confusing the contender and making him occupied with a defence position all the time.